2018
DOI: 10.1038/s41467-018-06148-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung colonization by Aspergillus fumigatus is controlled by ZNF77

Abstract: Aspergillus fumigatus is a critical pathogen of humans. Exposure to A. fumigatus conidia occurs frequently but is normally cleared from the respiratory airways. In contrast, individuals with respiratory diseases are often highly colonized by fungi. Here, we use genome-edited epithelial cells to show that the genetic variant rs35699176 in ZNF77 causes loss of integrity of the bronchial epithelium and increases levels of extracellular matrix proteins. These changes promote A. fumigatus conidial adhesion, germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 60 publications
1
41
1
Order By: Relevance
“…Moreover, culture-proven Aspergillus colonization occurs in up to 30% of patients with chronic obstructive pulmonary disease (COPD) (22). It has been found recently that Aspergillus colonization has a strong genetic basis associated with impaired expression of the transcriptional factor ZNF77 in bronchial epithelia, which leads to defective epithelial cell integrity and upregulation of extracellular matrix (ECM) proteins that facilitate conidial adhesion (23). Even though it is not always associated with infection, Aspergillus colonization is associated with a substantial increase in risk for development of invasive infection across a wide range of immunocompromised individuals (24).…”
Section: Spectrum Of Aspergillus Diseases: Clinical Manifestations Dmentioning
confidence: 99%
“…Moreover, culture-proven Aspergillus colonization occurs in up to 30% of patients with chronic obstructive pulmonary disease (COPD) (22). It has been found recently that Aspergillus colonization has a strong genetic basis associated with impaired expression of the transcriptional factor ZNF77 in bronchial epithelia, which leads to defective epithelial cell integrity and upregulation of extracellular matrix (ECM) proteins that facilitate conidial adhesion (23). Even though it is not always associated with infection, Aspergillus colonization is associated with a substantial increase in risk for development of invasive infection across a wide range of immunocompromised individuals (24).…”
Section: Spectrum Of Aspergillus Diseases: Clinical Manifestations Dmentioning
confidence: 99%
“…ZNF77 encodes a ubiquitously expressed transcription factor of yet unclarified importance. However, it has been suggested to have a role in vesicle trafficking and extracellular matrix regulation [38]. ACSBG2 is involved in fatty acid synthesis and is expressed solely in testicular and brainstem tissues [39].…”
Section: Discussionmentioning
confidence: 99%
“…Two aspects are believed to be important in its development, namely the persistence of fungi in the airways (due to abnormal clearance) and skewed hyper-immune T-helper 2 (Th2) response (possibly due to the HLA-DR2/DR5 bearing dendritic cells). In ABPA, several defects in innate and adaptive immunity have been identified that lead to persistence of A. fumigatus and a distorted immune response Table II 3 35 36 37 38 39 40 41 . Vitamin D deficiency has been proposed as a pathogenetic factor in ABPA complicating CF 42 43 ; however, its role in ABPA complicating asthma is uncertain 44 45 .…”
Section: Pathogenesis Of Abpamentioning
confidence: 99%
“… CHIT1 , chitotriosidase 1; CFTR, cystic fibrosis transmembrane conductance regulator; EEA1 , early endosome antigen 1; CARD9 , caspase recruitment domain-containing protein 9 Source : Refs 3 35 36 37 38 39 40 41 …”
Section: Pathogenesis Of Abpamentioning
confidence: 99%